Plasma levels of growth arrest specific protein 6 are increased in idiopathic recurrent pregnancy loss - (:unkn) unknown (VERDUCI PUBLISHER, 2014)
AIM: The aim of this study was to determine plasma Growth Arrest Specific Protein 6 (GAS6) protein levels in patients with unexplained recurrent pregnancy loss (RPL) and compare them to those of pregnant and to healthy non-pregnant women with a history of at least one live delivery. PATIENTS AND METHODS: A total of 205 women were included in the study. Of these, 68 were diagnosed with unexplained RPL and were not pregnant at the time of the study. The second group consisted of 67 pregnant women in the third trimester of pregnancy. The third group constituted the control group of 70 healthy non-pregnant women who had at least one live birth. Plasma levels of GAS6 protein were measured by ELISA. RESULTS: Mean plasma GAS6 levels were found to be different between RPL group and healthy non-pregnant women (12.17 +/- 4.39 mu g/L and 9.18 +/- 4.65, respectively, p = 0.0013). Although it was not statistically significant, plasma levels of GAS6 in the third trimester pregnant group (10.65 +/- 3.74 mu g/L) were found to be slightly higher than non-pregnant controls, and slightly lower than RPL group. In comparison of those with 2 or more than 2 pregnancy losses in the RPL group, there was no difference between these two subgroups in terms of GAS6 levels (12.39 +/- 4.27 mu g/L and 11.83 +/- 4.63 mu g/L, respectively, p = 0.62). CONCLUSIONS: Our findings revealed that plasma GAS6 levels were increased in patients with RPL. The prothombotic and proinflammatory nature of the GAS 6 protein makes it a likely culprit involved in the pathologic process in patients with RPL. Further studies are warranted to determine the possible role of GAS6 protein in the pathophysiology of idiopathic RPL.
Keywords: Growth arrest specific protein 6; Recurrent pregnancy loss; Idiopathic; Miscarriage; Thrombosis; Inflammation; TISSUE FACTOR; COAGULATION CASCADE; GAS6 RECEPTORS; GENE GAS6; ABORTION; INFLAMMATION; ACTIVATION; PLATELETS; INJURY; MICE